TEKNIK AUTOCOPY PADA SHARING FOLDER DALAM JARINGAN KOMPUTER - Ahmad Louis (JURNAL AKADEMIKA)
The computer network is sharing the resources of a computer that previously could only be used by the computer itself, can now be utilized in many computers, with the goal of keeping programs and data can be accessed in a kompuer another computer. Network kompuer make each user berbai files directly, the files are located in a specific folder can be shared on the network or placed on a file server, the result is a user on another computer can access it without difficulty because as accessible from kompuer own. Additionally some applications can be run from another computer in jaringan.Jaringan kompuer allows the user to communicate with a variety of media, such as email, newsgroups and video conferencing. This is possible because of text, voice, and video can be transmitted Dambar along a computer network as data